2000
DOI: 10.12693/aphyspola.97.1017
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of the Periodically Inhomogeneous Surface: Multiple Boundary Condition

Abstract: We deal with the following question: how can the composite nature of a boundary condition formulated for a periodically inhomogeneous surface and involving the composite surface parameter, be treated analytically? We show that when the appropriate Fourier transformation is applied, the composite boundary condition reduces to a specilic eigenproblem condition, which constitutes the spectrum of eigenvalues of an "effective" surface parameter, a novel quantity we introduced to account for the nonhomogeneity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
9
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 10 publications
3
9
0
Order By: Relevance
“…In particular, theoretically it has been shown that systems of continuous spins (XY and Heisenberg) in two dimensions (2D) with short-range interaction cannot have long-range order at finite temperature [4]. In the case of thin films, it has been shown that low-lying localized spin waves can be found at the film surface [5] and effects of these localized modes on the surface magnetization at finite temperature (T ) and on the critical temperature have been investigated by the Green's function technique [6,7]. Experimentally, objects of nanometric size such as ultrathin films and nanoparticles have also been intensively studied because of numerous and important applications in industry.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, theoretically it has been shown that systems of continuous spins (XY and Heisenberg) in two dimensions (2D) with short-range interaction cannot have long-range order at finite temperature [4]. In the case of thin films, it has been shown that low-lying localized spin waves can be found at the film surface [5] and effects of these localized modes on the surface magnetization at finite temperature (T ) and on the critical temperature have been investigated by the Green's function technique [6,7]. Experimentally, objects of nanometric size such as ultrathin films and nanoparticles have also been intensively studied because of numerous and important applications in industry.…”
Section: Introductionmentioning
confidence: 99%
“…Introduced in papers [8,9], the concept of surface pinning parameter A was proposed to describe the degree of freedom of surface spins in their precession. By definition the surface pinning parameter value A = 1 corresponds to the natural freedom of the surface spins resulting from breaking their bonds with neighbors eliminated from the system by surface cut.…”
Section: Surface Pinning Diagram Vs Swr Spectramentioning
confidence: 99%
“…Note, on the other hand, that we have previously [3][4][5] expressed this surface parameter in the frame of the SI model by the following equation:…”
Section: On Puttingmentioning
confidence: 99%
“…The fulfillment of the other condition (2) requires that |K surf (ϑ, ϕ) | → ∞, and an infinite value of the surface anisotropy constant is considered to result in a situation in which surface spins are completely pinned. * e-mail: henpusz@amu.edu.plWe will now show that the differential form of the RW equation written above is equivalent to the microscopic boundary equation derived within the surface inhomogeneity (SI) model; the latter is based on a discrete model of magnetization and has the form of difference equation [3,4]:where m 0 ≡ m surf is the surface amplitude of the transversal (dynamic) magnetization component m, and m −d is its analytical continuation beyond the surface, denoting the amplitude in the first fictitious layer parallel to the surface, separated from it by one lattice constant d. …”
mentioning
confidence: 96%
See 1 more Smart Citation